Diagnosis and treatment of patients with comorbid substance use disorder and adult attention-deficit and hyperactivity disorder: a review of recent publications. Issue 4 (July 2019) - van der Burg, Duco; Crunelle, Cleo L.; Matthys, Frieda; van den Brink, Wim
Abstract : Purpose of review: Attention-deficit and hyperactivity disorder (ADHD) often presents with comorbid substance use disorders (SUD). Due to similarities in key symptoms of both disorders and suboptimal efficacy of the available treatments, clinicians are faced with difficulties in the diagnosis and treatment of these patients with both disorders. This review addresses recent publications between 2017 and 2019 on the etiology, prevalence, diagnosis and treatment of co-occurring ADHD and SUD. Recent findings: ADHD is diagnosed in 15–20% of SUD patients, mostly as ADHD with combined (hyperactive/inattentive) presentation. Even during active substance use, screening with the Adult ADHD Self-Report Scale (ASRS) is useful to address whether further diagnostic evaluation is needed. After SUD treatment, the diagnosis of ADHD generally remains stable, but ADHD subtype presentations are not. Some evidence supports pharmacological treatment with long-acting stimulants in higher than usual dosages. Studies on psychological treatment remain scarce, but there are some promising findings on integrated cognitive behaviour therapy. Summary: Diagnosis and treatment of patients with comorbid ADHD and SUD remain challenging. As ADHD presentations can change during active treatment, an active follow-up is warranted to provide treatment to the individuals' personal strengths and weaknesses.